Inhibitory effects of in vivo oxidized high‐density lipoproteins on platelet aggregation: evidence from patients with abetalipoproteinemia. Issue 7 (18th March 2013) - Calzada, Catherine; Véricel, Evelyne; Colas, Romain; Guillot, Nicolas; El Khoury, Graziella; Drai, Jocelyne; Sassolas, Agnès; Peretti, Noël; Ponsin, Gabriel; Lagarde, Michel; Moulin, Philippe
Abstract : There is evidence that high‐density lipoproteins (HDLs) may regulate platelet function, but disparate results exist regarding the effects of oxidized HDLs on platelets. The objective of our study was to determine the role of in vivo oxidized HDLs on platelet aggregation. Platelet aggregation and redox status were investigated in 5 patients with abetalipoproteinemia (ABLP) or homozygous hypobetalipoproteinemia, two rare metabolic diseases characterized by the absence of apolipoprotein B‐containing lipoproteins, compared to 5 control subjects. Platelets isolated from plasma of patients with ABLP aggregated 4 to 10 times more than control platelets, depending on the agonist. By contrast, no differences in the extent of platelet aggregation were observed between ABLP platelet‐rich plasma (PRP) and control PRP, suggesting the presence of a protective factor in ABLP plasma. ABLP HDLs inhibited agonist‐induced platelet aggregation by binding to SR‐BI, while control HDLs had no effect. On the other hand, lipoprotein‐deficient plasma from patients with ABLP did not inhibit platelet aggregation. Severe oxidative stress was evidenced in patients with ABLP. Compared to control HDLs, ABLP HDLs showed a 40% decrease of α‐tocopherol and an 11‐fold increased malondialdehyde concentration. These results demonstrate that in vivo oxidized HDLs do not lose their antiaggregatory properties despite oxidation.—Calzada, C., Véricel, E., Colas, R., Guillot, N., El Khoury, G., Drai, J., Sassolas, A., Peretti, N., Ponsin, G., Lagarde, M., Moulin, P. Inhibitory effects of in vivo oxidized high‐density lipoproteins on platelet aggregation: evidence from patients with abetalipoproteinemia. FASEB J. 27, 2855–2861 (2013). www.fasebj.org